Capacitive-type liquid crystal temperature sensor. Issue 8 (21st June 2021) - Jing, Shuai; Gao, Na; Tang, Zongyuan; Wu, Keming; Sun, Jingjing; Cai, Minglei; Zhao, Tongzhou; Yang, Changyong; Xing, Hongyu; Ye, Wenjiang
ABSTRACT: Temperature monitoring plays an increasingly important role in research and industrial applications. Based on the influence of liquid crystal material thermal sensitivity on the capacitance of liquid crystal cell, the sensing performance of the capacitive-type liquid crystal temperature sensor were studied. By testing the capacitance under the voltage from 0 V to 20 V at different temperatures, the capacitance–voltage curve is drawn, and then the relationship between the capacitance change rate and the temperature at different voltages was obtained, so as to analyse its sensitivity. The results show that the capacitance of the liquid crystal material (RDP-09 T-100) is linearly related to the temperature in the temperature range of 20–110°C, even when the applied voltage is 0.1 V, which proves its feasibility as a temperature measuring medium for the temperature sensor and shows that the sensor has the advantage of low power consumption. When the applied voltage is 15 V, the sensitivity of the capacitive-type liquid crystal temperature sensor can reach 0.94 pF/°C and its response time is 0.115 s/(pF.°C). This research further expands the application scope of liquid crystal and has certain guiding significance for the development of new temperature sensor. Graphical abstract: uf0001